Myth, Identity, and Conflict: A Comparative Analysis of Romanian and Serbian Textbooks - Segesten, Anamaria Dutceac (Lexington Books, 2011)
Myth, Identity, and Conflict: A Comparative Analysis of Romanian and Serbian Textbooks, by Anamaria Dutceac Segesten, is an examination of how history and politics became entangled in Romania and Serbia. In it, Segesten asks questions like: Is myth present in the history textbooks of Romania and Serbia? If so, are there differences in the ways these myths define the in-group and the relationship with the Other between a country that experienced interethnic conflict (Serbia) and a country that did not (Romania)? Do textbooks affect the odds that conflict will occur? Segesten's findings confirm the presence of mythologized versions of the past in the history textbooks of both countries over the entire fifteen-year period studied (1992–2007), despite claims for professionalization of textbook-making. Myths of noble origins, of heroism and victimhood, appear in both cases. Segesten finds the language to be ideological and in favor of the ethnic majority, even if over time there is a slow tendency towards moderation (especially in Romania), probably due to the influence of the European Union. Ultimately, Myth, Identity, and Conflict, by Anamaria Dutceac Segesten, questions the alleged power of history textbooks to make a difference in ethnically divided societies prone to conflicts.